Bananas in the aftermath of La Palma volcanic eruption (Canary Islands, Spain): A study on the nutritional and toxic element composition of post-disaster production - Ángel Rodríguez-Hernández; Norberto Ruiz-Suárez; Luis Alberto Henríquez-Hernández; Ricardo Díaz-Díaz; Manuel Zumbado; María del Mar Bernal Suárez; Pablo Alonso-González; Eva Parga-Dans; Octavio P. Luzardo (PLoS ONE, 2025)
The 2021 Tajogaite eruption on La Palma devastated banana production, a key crop, with a 50% loss (53,000 tons). Concerned about potential contamination from volcanic ash and magma, we investigated the elemental composition of bananas from the eruption area and control sites. Inductively Coupled Plasma Mass Spectrometry (ICP-MS) analysis quantified both essential and non-essential mineral elements, including potentially toxic elements identified by the Agency for Toxic Substances and Disease Registry (ATSDR), as well as rare earth elements (REEs) and other trace elements that are scarcely studied under volcanic conditions. This approach allowed for spatial and temporal comparisons. Results showed a decrease in element levels post-eruption; however, samples from the volcanic area still exhibited elevated concentrations of Fe, Co, Cd, Al, Ba, Ni, Sn, Sr, Ti, V, and REEs. Control samples from unaffected islands with higher anthropogenic pressure showed elevated levels of Mn and Mo. Despite the increased element levels, banana consumption remains safe and constitutes a valuable source for the recommended daily intake of Mo and Co. Most toxic elements were present at less than 1% of the tolerable daily intake (TDI), with the highest values for As and V reaching 3%, and no risk was associated according to the margin of exposure approach. This eruption highlights the need for continuous monitoring in volcanic regions to safeguard public health and food safety.